Role of colors in prosthodontics: Application of color science in restorative dentistry - Vinaya Bhat; D Krishna Prasad; Sonali Sood; Aruna Bhat (Wolters Kluwer Medknow Publications, 2011)
Shade selection procedure depends on various factors including translucency, contour and surface texture. Tooth shade selection using a conventional means involves a high degree of subjectivity. Traditional shade guides are available that use several methods for quantifying shade. Technology-based systems provide with an advantage of natural looking restorations. They include RGB devices, colorimeters, spectrophotometers. The impact of the color science can be seen on various restorative materials ranging from ceramics to maxillofacial prosthetic materials.